Comparison of Several Linear Ordering Methods for Selection of Locations in Order‑picking by Means of the Simulation Methods - Dmytrów, Krzysztof (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
When a company uses a shared storage system, selection of locations during the order‑picking process is not an obvious task. Every location where the picked product is placed, can be described by means of several variables, such as: storage time, distance from the I/O point, degree of demand satisfaction, or the number of other picked products in the order. Therefore, the “attractiveness” of each location from the point of view of a certain order can be described by means of synthetic variable, on the basis of which a ranking is created. For each product, the decision‑maker selects the highest‑ranking locations and designates a route for the picker. In the article, by means of the simulation methods, results obtained by several classification methods will be compared. These methods are: Taxonomic Measure of Location’s Attractiveness (based on the Hellwig’s Composite Measure of Development), the TOPSIS method with the Euclidean and GDM distances and the Generalised Distance Measure used as the composite measure of development.